2016
DOI: 10.1002/chem.201504792
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Reactions of Neutral Phosphidozirconocene Complexes as a Convenient Entry into Frustrated Lewis Pair Territory

Abstract: Neutral phosphidozirconocene complexes [Cp2Zr(PR2)Me] (Cp=cyclopentadienyl; 1a: R=cyclohexyl (Cy); 1b: R=mesityl (Mes); 1c: R=tBu) undergo insertion into the Zr-P bond by non-enolisable carbonyl building blocks (O=CR'R''), such as benzophenone, aldehydes, paraformaldehyde or CO2, to give [Cp2Zr(OCR'R''PR2)Me] (3-7). Depending on the steric bulk around P, complexes 3-7 react with B(C6F5)3 to give O-bridged cationic zirconocene dimers that display typical frustrated Lewis pair (FLP)/ambiphilic ligand behaviour. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 86 publications
6
22
0
Order By: Relevance
“…The Δ δ ( m , p ‐F) values of Ti6 ( δ =2.6 ppm), Zr6 ( δ =2.5 ppm), and Hf6 ( δ =2.6 ppm) are in good accordance to other characterized cationic complexes, in which the MeB(C 6 F 5 ) 3 – anion is noncoordinating, e.g. Δ δ ( m , p ‐F) = 2.6 ppm for the activation product of Cp 2 Zr(Me)OC q (Fc)PCy 2 , B(C 6 F 5 ) 3 and [Pd(C 3 H 5 )Cl] 2 . Furthermore, the M + signals of Ti6 , Zr6 , and Hf6 were detected by high‐resolution ESI mass spectrometry.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The Δ δ ( m , p ‐F) values of Ti6 ( δ =2.6 ppm), Zr6 ( δ =2.5 ppm), and Hf6 ( δ =2.6 ppm) are in good accordance to other characterized cationic complexes, in which the MeB(C 6 F 5 ) 3 – anion is noncoordinating, e.g. Δ δ ( m , p ‐F) = 2.6 ppm for the activation product of Cp 2 Zr(Me)OC q (Fc)PCy 2 , B(C 6 F 5 ) 3 and [Pd(C 3 H 5 )Cl] 2 . Furthermore, the M + signals of Ti6 , Zr6 , and Hf6 were detected by high‐resolution ESI mass spectrometry.…”
Section: Resultssupporting
confidence: 73%
“…Synthesis of L3: Compound L3 was synthesized according to a slightly modified literature procedure . To a solution of potassium diphenylphosphide (21.4 mL, 10.70 mmol; 0.5 m in THF) at reflux, was added a solution of 2‐fluoroacetophenone (1.3 mL, 10.70 mmol) in THF.…”
Section: Methodsmentioning
confidence: 99%
“…1:1molar ratio based on 1 HNMR spectroscopy), probablyo wing to the coexistence of the unsymmetrical Sc centera nd the inherently chiral carbon atom in the MMBL fragment. [20] With this promising stoichiometric reactivity,w en ext investigated utilizing RE/P complexes as catalysts for the polymerization of the above-mentioned conjugated polar alkenes.T he research groupso fC hen [21] and Rieger [22] reported the use of main-group Lewis-acid Al-or B-based Lewisp airs for the polymerization of polar alkenes. Our three rare-earth metal-containing Lewis pairs 8-10 were activet oward the polymerization of MMA,M BL, and MMBL in tolueneo rc hlorobenzene (PhCl) at room temperature and the results are summarized in Ta ble 1.…”
mentioning
confidence: 99%
“…Cp 2 Zr(CH 3 )(OR)]. If the comparison is restricted to just the latter structures, the Zr-C bond length range is somewhat narrower from 2.26-2.33 Å with a median of 2.29 Å (Bestgen et al, 2016;Black et al, 2008;Breen & Stephan, 1996;Chapman et al, 2012;Frö mel et al, 2013;Gambarotta et al, 1985;Jian et al, 2018;Koch et al, 2000;Mariott & Chen, 2005;Matchett et al, 1988;Normand et al, 2016;Stuhldreier et al, 2000). There are 15 structures containing siloxide ligands bonded to a zirconocene unit in a pseudo-tetrahedral environment used to compare Zr-O and O-Si distances in 1.…”
Section: Database Surveymentioning
confidence: 99%
“…AQESIZ (Mukherjee et al, 2011); AXIBOA (Boulho et al2016); BESGOW (Bolig & Chen, 2004); BODMIR (Helmstedt et al, 2008); BUHVAD (Xu et al, 2015); BUYSOD10 (Longato et al, 1985); CADRUU (Hunter et al, 1983); COHTEY (Waymouth et al, 1984); COPRII (Ho et al, 1984); DAGKAX and DAGKIF (Gambarotta et al, 1985); DITHAP (Martin et al, 1985); EHEFUT (Neu et al, 2011); EKEVEX, EKEVIB, EKEVOH, EKEVUN, EKEWAU and EKEWEY (Normand et al, 2016); ESISAA (Zuccaccia et al, 2004); GIPYUZ (Matchett et al, 1988); HEMCOR (Askham et al, 1994); HIKHUF and HIKJAN (Gurubasavaraj et al, 2007); HUVLAL (Fujdala et al, 2003); IGUDOD (Hü erlä nder et al, 2002); JITVAK and JITVEO (Mandal et al, 2007); JUGCIZ (Boulho et al, 2015); KEXYER (Erker et al, 1990); KODQAV (Koch et al, 2000); KUPQAP (Mariott & Chen, 2005); LEDBEB (Askham et al, 1993); LEPXAH (Mukherjee et al, 2013); MOJHEZ (Black et al, 2008); NAHYOL (Bai et al, 2005); NAPXUY (Pineda et al, 2005); NIMNOM (Johnson et al, 1997); ODOBIU, ODOBOA and ODOBUG (Frö mel et al, 2013); OKUFUX (Bestgen et al, 2016); OZUCAO (Kelsen et al, 2011); PEDFUA (Singh et al, 2006); QIZCEI ; REDTUQ (Cummings et al, 2006); TIWKUG (Yang, Schulz et al, 2008); TOWMUN (Breen & Stephan, 1996); VIBSOO (Waymouth et al, 1990); WAJLO...…”
Section: Figurementioning
confidence: 99%